Caracterização do uso atual de medicamentos por mulheres adultas e fatores associados: estudo de base populacional no sul do Brasil - Mottin, Vitória Hana Müller (Universidade do Vale do Rio dos Sinos, 2019)
Medicines consist in high use technologies for prevention and treatment of a series of health conditions. Medicine utilization studies are of huge importance for public health, considering that the irrational use of medicines may cause harm to the users and economic losses for the individuals and the health system. OBJECTIVE: To assess current medicine use and its associated factors in adult women living in the urban area of São Leopoldo, RS. METHODS: Cross-sectional population-based study with women from 20 to 69 years old resident in the urban area of São Leopoldo, RS, Brazil. A multi-stage sampling was conducted with random selection of 45 census tracts. Current medicine use was analyzed including all reported medicines and excluding specific contraceptive use. The independent variables consisted in demographic, socioeconomic, behavioral, anthropometric, health and use of health services’ characteristics. Analyses were performed using Poisson Regression with robust variance. RESULTS: A total of 1.128 women were interviewed. Current medicine use was reported by 66.7% (IC95% 63.9-69.3). Excluding the specific use of contraceptives, the prevalence of medicine use was 55.1% (IC95% 51.9-58.2). After adjustment, a higher age, household income per capita, number of chronic morbidities, number of medical appointments and worse self-rated health, as well as not having an occupation and not consuming alcohol were associated to both outcomes. Having a health insurance plan was associated only to current medicine use. Higher Body Mass Index and lower education were only associated to current medicine use after the exclusion of specific contraceptive use. CONCLUSION: This study revealed an elevated prevalence of current medicine use and provided information about the groups of higher exposure to medicine use, which should be considered priority for medicine access strategies. Modifiable risk factors must be of special interest in adult women, once they may contribute in the prevention of chronic conditions and early use of multiple medicines.
Keywords: Uso de medicamentos; Mulheres; Adulto; Inquéritos epidemiológicos; Farmacoepidemiologia; Drug utilization; Women; Adult; Health surveys; Pharmacoepidemiology; ACCNPQ::Ciências da Saúde::Saúde Coletiva